2017
DOI: 10.1002/pnp.476
|View full text |Cite
|
Sign up to set email alerts
|

Improving the referral process from primary care to an AMHT

Abstract: There is established evidence that discrepancy rates in referral thresholds from GPs to secondary care services as high as 10‐fold exist between individual GPs. Andrew Molodynski et al looked systematically at the amount and quality of referrals to the secondary care team in order to identify any issues and develop support for referrers to make the process as smooth as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…There is considerable information on referral from GPs in the primary care sector to secondary care internationally [ 13 , 15 19 , 23 ]. Unlike in the current study, these studies [ 18 , 19 , 23 ] showed that the majority of referrals came from GPs. Based on the aforementioned findings that GPs often refer patients according to their symptomatic picture rather than with a confirmed diagnosis [ 17 , 24 , 25 ], we expected that our findings would also comprise of a considerably higher proportion of patients referred from GPs.…”
Section: Discussioncontrasting
confidence: 69%
“…There is considerable information on referral from GPs in the primary care sector to secondary care internationally [ 13 , 15 19 , 23 ]. Unlike in the current study, these studies [ 18 , 19 , 23 ] showed that the majority of referrals came from GPs. Based on the aforementioned findings that GPs often refer patients according to their symptomatic picture rather than with a confirmed diagnosis [ 17 , 24 , 25 ], we expected that our findings would also comprise of a considerably higher proportion of patients referred from GPs.…”
Section: Discussioncontrasting
confidence: 69%
“…Another model limitation relates to patient priority. The model assumes first-come first-served, whereas order of service is realistically dependent on priority levels assigned to the referrals [38] .…”
Section: Discussionmentioning
confidence: 99%
“…The Department of Health estimates that mental health difficulties cost the UK economy between £70bn and £100bn per year (Davies, 2013). With a high prevalence of poor mental health in the UK, mental health services can often be overstretched and insufficiently funded (Dehghan et al , 2017). The associated level of work for practitioners can also mean that services are at risk of acquiring long waiting lists (Marzillier & Hall, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The associated level of work for practitioners can also mean that services are at risk of acquiring long waiting lists (Marzillier & Hall, 1999). Hence, resource allocation is vital to ensure care is provided in the most appropriate setting and that there are efficient pathways to specialist care for those who need it (Dehghan et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation